PENGARUH MEDIA STIMULASI GAMBAR TERHADAP KEMAMPUAN MEMBACA SISWA DI KELAS II SD NEGERI 105286 TANDAM HILIR I - Ririn Safarina; Fahmi Ashari S Sihaloho; Rizka Hidayah Husin Lubis (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2020)
This study aims to: (1) Analyze the reading abilities of second-grade students before the application of visual stimulation at SD Negeri 105286 Tandam Hilir I, and (2) Test and analyze whether the visual stimulation method using image media affects the reading abilities of second-grade students at SD Negeri 105286 Tandam Hilir I. This study is an experimental research. The subjects are second-grade students at SD Negeri 105286 Tandam Hilir I, totaling 19 students. The method used in this study is the experimental method. The research design used is the One Group Pretest-Posttest. This trial did not use a control group. The design was implemented by comparing the pretest and posttest results in the tested group. The results of this study indicate that students' observation and attention to images can enhance their reading abilities. There is a difference between the pretest and posttest scores of the second-grade students at SD Negeri 105286 Tandam Hilir I.